Synthesis and antiproliferative properties of a new ceramide analog of varacin. (January 2016) - Mahendran, Adaickapillai; Ghogare, Ashwini A.; Bittman, Robert; Arthur, Gilbert; Greer, Alexander
Highlights: A new ceramide polysulfur conjugate was synthesized. Antiproliferative activity was examined against breast, prostate, pancreas and cervix cancer cells and glioblastoma. The bioactive properties were compared to a PEGylated polysulfane and a benzenedithiol which lacks the polysulfur ring. The polysulfur ring is needed for biological activity. Abstract: A benzopentasulfane was synthesized in 8 steps with a ceramide attached through an amide bond to the 7-position of the heterocycle structure. The anticancer activity of this synthetic ceramide–benzopolysulfane drug conjugate was analyzed against five human cancer cell lines MDA-MB-231 (breast), DU145 (prostate), MIA PaCa-2 (pancreas), HeLa (cervix), and U251 (glioblastoma). The ceramide–benzopolysulfane conjugate had IC50 values ranging from 10 to >20 μM with complete cell killing at 12.5 μM for MDA-MB-231 and 20 μM for DU145 and HeLa cells. The ceramide–benzopolysulfane conjugate had IC50 values 1.8 and 4.0 times lower than a PEG benzopolysulfane, N -(2-(2-(2-methoxyethoxy)ethoxy)ethyl)benzo[ f ][1, 2, 3, 4, 5]-pentathiepine-7-carboxamide, for MDA-MB-231 and DU145 cells, respectively. The parent "unsubstituted" benzopolysulfane, o -C6 H4 S5, had IC50 values 4.2 times lower and 2.7 times higher than the ceramide benzopolysulfane for MDA-MB-231 and DU145 cells, respectively. The results indicate that the polysulfur linkage is needed for activity since benzenedithiol, o -C6 H4 (SH)2, had IC50 values greater than 30 μM with little effect on MDA-MB-231 and DU145 cells. Thus, to account for the bioactivity, a bimolecular reaction of cellular thiol with the ceramide benzopolysulfane is a proposed followed by thiozone (S3 ) extrusion.